Profitability relation, corporate social responsibility fund, and environmental performance with firm value (Study at companies listed in the sustainable and responsible investment index (SRI)–Kehati) - Yuliana, Indah (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2019)
The paradigm of a company that was originally only oriented to profit has shifted to the tripple bottom line, namely not only concerned with economic interests, but also commitment to the environment (planet) and people (people). This study aims to determine the effect of profitability and funds on Corporate Social Responsibility on corporate value and to determine environmental performance as a moderating variable on the relationship of profitability and funds of Corporate Social Responsibility to the value of the company. The population in this study are companies included in the SRI-Kehati Index 2013-2016. The sample of research is 12 companies taken by purposive sampling technique. Data analysis method used is multiple linear regression analysis and Moderate Regression Analysis (MRA). The results showed that profitability has a positive and significant effect on firm value. Conversely, Corporate Social Responsibility funds have no effect and insignificant to the value of the company. While environmental performance is significantly able to moderate the relationship between profitability and Corporate Social Responsibility funds to company value.